Borja Albi, A., & Prieto Ramos, F. (Eds). Legal translation in context: Professional issues and prospects. - Harvey, Malcolm (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
Borja Albi, A., & Prieto Ramos, F. (2013). Legal translation in context: Professional issues and prospects. Bern: Peter Lang. 315 p.